WAITING-LINE MANAGEMENT AND REPEAT PATRONAGE OF FAST FOOD CENTRES IN RIVERS STATE, NIGERIA - NDU, EUGENE CHIGOZIE; BISSONG, NNEKA IFEOMA (American Journals Publishing, 2023)
This study investigated the relationship between waiting-line management and repeat patronage of fast food centres in Rivers State, Nigeria. Primarily, it examined the effect of waiting-line management strategies dimensioned by customer engagement, staff empathy, waiting environment and perceived waiting time on repeat patronage. It was hypothesized that there is no significant relationship between each of these dimensions and repeat patronage; giving rise to four hypotheses. Cross-sectional survey design was adopted for the study; and data were obtained from 384 customers of 15 major fast food centres in Rivers State. This was subjected to statistical analysis using Partial Least Square Structural Equation Modelling (PLS_SEM) aided by SMART PLS. The results showed that customer engagement, staff empathy, waiting environment and perceived waiting time all had significant positive correlations with repeat patronage at beta (β) values of 0.574, 0.630, 0.489 and 0.591 respectively. This affirmed that waiting-line management is a veritable predictor of repeat patronage. Consequentially, managers of fast-food centres are urged to design and implement efficient and effective waiting-line management systems geared towards enhancing customers’ satisfaction and loyalty for continuous patronage. In doing this, priority attention should be given to waiting environment and staff empathy.
Keywords: Customer Engagement, Perceived Waiting time, Repeat Patronage, Staff Empathy, Waiting Environment